PERANCANGAN RANGKA MESIN CNC ROUTER SEBAGAI ALAT PENUNJANG DALAM PEMBUATAN POLA CETAKAN PADA PENGECORAN LOGAM SKALA LABORATORIUM - Ressy Noor Rafiq; Besse Titing Karmiati; Manty Aldilani Ikanigsih; Lulu Nurdini; War An Rosihan (Jurnal Teknologi Terpadu, 2026)
The development of the metal casting industry requires technology capable of producing products with complex shapes and high precision. This study focuses on the design and analysis of the CNC Router machine frame on a laboratory scale to support mold pattern fabrication in metal casting practicals at Jenderal Achmad Yani University. The frame, constructed from aluminum profile 2040 and ABS material, was analyzed using the Finite Element Method (FEM) through SolidWorks Simulation to evaluate stress distribution, safety factor, and total deformation. The simulation results show a maximum Von Mises stress of 0.1771 MPa, a maximum safety factor of 15, and a maximum total deformation of 0.001409 mm. These results indicate that the designed frame possesses excellent strength, rigidity, and stability under operational loads. Therefore, the CNC Router frame is feasible for manufacturing and can support efficient, technology-based metal casting practicals.